The Real-World Ethics of Adaptive-Design Clinical Trials - Bothwell, Laura E. (The Hastings Center report, 2017)
From the earliest application of modern randomized controlled trials in medical research, scientists and observers have deliberated the ethics of randomly allocating study participants to trial control arms. Adaptive RCT designs have been promoted as ethically advantageous over conventional RCTs because they reduce the allocation of subjects to what appear to be inferior treatments. Critical assessment of this claim is important, as adaptive designs are changing medical research, with the potential to significantly shift how clinical trials are conducted. Policy-makers are swiftly moving to encourage greater use of adaptive designs. In 2016, the newly enacted 21st Century Cures Act instructed the Food and Drug Administration to help product sponsors incorporate adaptive methods into proposed clinical trial protocols and applications for investigational drugs and also biological products. In this article, we review the ethical justifications commonly offered for adaptive designs, explore these arguments in the context of actual trials, and contend that clinical equipoise is a useful standard for adaptive-trial ethics. We distinguish between theoretical and clinical equipoise and explain why ethical arguments related to adaptive trials tend to focus on the former. Yet we contend that theoretical equipoise can be an unreliable standard for adaptive ethics. While we contend that clinical equipoise is the most critical principle for the primary ethical concerns posed by adaptive trials, we suggest ethical approaches to deal with some additional concerns unique to adaptive designs.